2012
DOI: 10.1002/bjs.8688
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of antibiotics in acute uncomplicated diverticulitis13

Abstract: Antibiotic treatment for acute uncomplicated diverticulitis neither accelerates recovery nor prevents complications or recurrence. It should be reserved for the treatment of complicated diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
314
2
22

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(344 citation statements)
references
References 16 publications
6
314
2
22
Order By: Relevance
“…При невыраженной клинической симптоматике и доста-точной уверенности в отсутствии более тяжелых ослож-нений антибактериальные препараты можно не назна-чать (УД-1b; CP-A) [9,27,28].…”
Section: острый неосложненный дивертикулитunclassified
“…При невыраженной клинической симптоматике и доста-точной уверенности в отсутствии более тяжелых ослож-нений антибактериальные препараты можно не назна-чать (УД-1b; CP-A) [9,27,28].…”
Section: острый неосложненный дивертикулитunclassified
“…37 These findings encouraged a randomised controlled trial of antibiotics in patients with acute uncomplicated acute diverticulitis from Sweden, which reported no difference in complications such as abscess or perforation between those treated with or without antibiotics with a median length of stay in both groups of 3 days. 63 This study, however, was criticised for excluding patients with sepsis (though no definition of sepsis was provided) and for problems with possible selection bias, given that not all patients eligible for the study were recorded. It remains to be seen if these results are generalisable.…”
Section: Conservative/medicalmentioning
confidence: 99%
“…These results should be interpreted with caution, as neither study was randomized, and the impact of selection bias on the outcomes must be considered. A recent Cochrane review concluded that there were no significant differences in outcomes whether or not antibiotics were given, although this was based on a single randomized controlled trial [20] and was accompanied by a recommendation that confirmation from further randomized trials should be obtained before incorporating these findings into clinical practice [15]. It appears that although this approach may not be appropriate for all patients, the potential for omitting antibiotics in selected patients with radiologically confirmed uncomplicated diverticulitis does exist.…”
Section: Management Of Acute Uncomplicated Diverticulitismentioning
confidence: 99%